ECONOMIC EVALUATION OF LETTUCE FERTILIZED WITH BIOMASS OF Calotropis procera IN TWO GROWING SEASONS - Flor Souza, Enio Gomes; Sousa Santana, Falkner Michael de; Menezes Martins, Bruno Novaes [UNESP]; Leal, Ygor Henrique; Barros Junior, Aurelio Paes; Silveira, Lindomar Maria da (Univ Fed Rural Semi-arido-ufersa, 2019)
Vegetable production is an impactful activity, characterized by intensive land use, high input demand, and it requires strategic management adoption, especially in sustainable production systems, where the pillars of sustainability (environmental, social and economic) must be respected. In this sense, the objective of this work was to evaluate economic indicators of lettuce production using Caatinga spontaneous species (Calotropis procera: rooster tree) as fertilizer and cultivated in two seasons (spring and fall-winter) in the municipality of Serra Talhada, PE. The experimental design was in randomized blocks, arranged in a 4 x 4 factorial scheme, with three replications. The first factor was the biomass amounts of green manure (5.4, 8.8, 12.2 and 15.6 t ha(-1) on a dry basis); and the second was their incorporation times in the soil (0, 10, 20 and 30 days before lettuce transplanting). The green mass yield, production costs, rate of return, and net profit margin were determined. The amount 15.6 t ha(-1) of C. procera allowed higher profitability to the organic production of lettuce, and it is considered ideal to incorporate the green manure 11 (spring) and 15 (fall-winter) days before transplanting the vegetable. The spring crop promoted a superior economic return to the fall-winter planting, demonstrating economic viability even in the smallest amount of C. procera.
Keywords: Lactuca sativa L.; Rooster tree; Organic farming; Profitability